2014
DOI: 10.1177/0218492314545620
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of coronary artery bypass grafting in a tertiary-care center in Pakistan

Abstract: Our comparable results and international data advocate revision of the current practice of using percutaneous coronary intervention over coronary artery bypass in the developing world. Institutional results are essential to determine the outcome of coronary artery bypass in high-risk populations with a high burden of diabetes and hypertension. We noted increased complications and mortality in patients with left main rather than multivessel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“… 5 An overall mortality after CABG has been estimated to be 3.4%. 6 Secondary prevention of CHD and rehabilitation of cardiac patients after revascularization is of utmost importance in reducing the mortality associated with this disease and achieving the best possible physical, mental and social wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“… 5 An overall mortality after CABG has been estimated to be 3.4%. 6 Secondary prevention of CHD and rehabilitation of cardiac patients after revascularization is of utmost importance in reducing the mortality associated with this disease and achieving the best possible physical, mental and social wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…But we have remained successful to prove that timely surgical intervention, adequate pre-operative management, and regular follow-up are keys to successful outcomes at a newly developed cardiac surgery institute. Institutional results are essential to enable surgeons to determine whether international data are in keeping with local findings [13]. NICVD Sukkur being first of its kind government-funded state of the art cardiac surgical facility has demonstrated impressive surgical results compared with reliable Western standards.…”
Section: Diagnosis and Procedures Frequencymentioning
confidence: 99%
“…(4) CABG was allocated to the American and European Guidelines as a Class-1A indication for multi-ship revascularization. (5) An overall CABG death rate of 3.4 percent was estimated (6) Secondary prevention of CHD and cardiac rehabilitation Patients who have been revascularized are highly necessary to minimize their mortality, and maintain the best possible physical, mental and social well-being.Growing literature has shown that interventions to life style, beneficial modifications to the risk factor and selective use of prophylactic medication scans have decreased the risk of non-fatal and fatal in CHD patients. (7) The importance of dietary improvement, exercise and prophylactic drug therapies is clearly illustrated in existing guidelines.…”
Section: Introductionmentioning
confidence: 99%